(untitled) (Journal of Asian Development Studies, 2025)
The main objective of the current study is to examine the nexus between board attributes and a firm’s sustainability practices. These practices (ESG) attract policymakers, researchers, and regulators due to the rapid increase in global environmental degradation. This study explains how board characteristics like size, independence, and gender diversity contribute to firms’ sustainable (ESG) practices. The study uses firm-specific data from four developed economies (China, the UK, Germany, and Japan) during 2017 and 2022. To achieve objectives, the study uses statistical tools like ordinary least squares (OLS) and fixed effect models. The study findings reveal that board characteristics like board size, independence, and gender diversity positively and significantly influence a firm’s sustainability practices. This highlights the critical role of governance mechanisms in promoting sustainability practices. The result affirms that sustainability practices (ESG), with practical board attributes, are no longer optional but essential. The research outcome encourages policymakers and management to prioritize board attributes significantly enhancing a firm’s sustainability practices. This study addresses the limited literature on the nexus between board-specific attributes and firm-level sustainability, offering valuable insights into this critical nexus.